230k views
4 votes
Perform the indicated operation. (y4 - 1) ÷ (y + 1)

2 Answers

3 votes

Answer: y^3 - y^2 + y - 1


Step-by-step explanation: Factor the numerator and denominator and cancel the common factors. This should leave you with y^3-y^2+y-1.

User Melynda
by
5.2k points
5 votes


The\ domain:\\D:y\\eq-1\\\\(y^4-1)/(y+1)=((y^2)^2-1^2)/(y+1)=((y^2-1)(y^2+1))/(y+1)\\\\=((y-1)(y+1)(y^2+1))/(y+1)=(y+1)(y^2+1)=y^3+y^2+y+1\\\\Used:\\(a^n)^m=a^(nm)\\\\a^2-b^2=(a-b)(a+b)

User Lew Wei Hao
by
5.7k points